Platelet function and microparticle levels in atrial fibrillation: Changes during the acute episode. (15th September 2017) - Pourtau, Line; Sellal, Jean Marc; Lacroix, Romaric; Poncelet, Philippe; Bernus, Olivier; Clofent-Sanchez, Gisèle; Hocini, Mélèze; Haïssaguerre, Michel; Dignat-George, Françoise; Sacher, Frédéric; Nurden, Paquita
Abstract: Background: Thrombotic risk constitutes a major complication of atrial fibrillation (AF). Platelets and microparticles (MPs) are important for hemostasis and thrombosis, however their participation during AF is not well known. The aim of this study was to characterize platelet function and MPs procoagulant and fibrinolytic activity in AF patients and to determine the effects of an acute-AF episode. Methods: Blood was collected from paroxysmal (21) and persistent (16) AF patients referred for AF catheter ablation. Ten patients in sinus rhythm for 10 days were induced in AF allowing comparisons of left atrium samples before and after induction. Platelet aggregation with ADP, TRAP, collagen, and ristocetin was studied. Platelet surface expression of PAR-1, αIIbβ3, GPIb and P-selectin were evaluated by flow cytometry, and MPs-associated procoagulant and fibrinolytic activity levels were determined by functional assays. Results: A specific reduction in platelet aggregation to TRAP, activating the thrombin receptor PAR-1, was found in all AF patients. No differences in platelet receptor expression were found. Yet, after acute-induced AF, the platelet response was improved. Furthermore, a significant decrease of left atrium tissue factor-dependent procoagulant activity of MPs was observed. Conclusion: Acute episodes of AF results in a decrease in MPs-associated tissue factor activity, possibly corresponding to consumption, which in turn favors coagulation and the local production of thrombin. A decreased platelet basal aggregation to TRAP may result from PAR1 desensitization, whereas the improved response after an induced episode of AF suggests activation of coagulation and PAR1 re-sensitization.